Empirics vs. art theory: Exploring a factor structure of pictorial expression based on contemporary artworks - Schoch, Kerstin; Ostermann, Thomas (Creativity research journal, 2025)
The RizbA scale combines psychometrics and art theory and enables a measurement of pictorial expression. This study explores its factor structure and a potential gap between theory and empirics. A sample of 275 pictorial works by artists and nonprofessionals was rated by 179 art experts. Three CFA path models were specified: models A and B based on the empirical results of previous studies, C on the theory of the initial study. Model C was additionally tested on a combined dataset. A and B did not converge, C was associated with fit indices as follows: RSMEA = .122, CFI = .712, TLI = .679, SRMR = .135, for the combined dataset: RSMEA = .086, CFI = .740, TLI = .696, SRMR = .084. Only model C partly suggests an acceptable fit. The results speak to a methodological gap between empirics and theory, that might be solved by a postdisciplinary measurement model.